La performance virtuale del sé nelle arti digitali dal vivo. Prospettive millennials fra Italia e Corea - Federica Patti (Antropologia e Teatro)
How do we define the self, individually and collectively, in the age of artificial intelligence and the metaverse? Starting from two case studies, and following a research perspective that can be placed in the field of digital live art disciplines, this article presents and analyses productions in dialogue with each other, to outline a general international – and internet-based – contemporary trend that brings together the artistic languages of Korean and Italian cultural origins, especially among the millennial generation. The common denominator is the interlocution and the development of artificial intelligence systems that, in the hands of artists, can express a creative agency that redefines the concept of monadic – and almost exclusively human – authorship.